Unusual diversity in alpha-amanitin sensitivity of RNA polymerases in trichomonads - Vanácová, S; Tachezy, J; Ullu, E; Tschudi, C (Molecular and biochemical parasitology, 2001)
Previous studies in the parasitic protist Trichomonas vaginalis have revealed that protein coding genes are transcribed by an alpha-amanitin-resistant RNA polymerase (RNAP) II. To investigate whether this unusual property is a general characteristic of trichomonads, we addressed the physiology of RNA synthesis in lysolecithin-permeabilized cells. Unlike in T. vaginalis, RNAP II in Tritrichomonas foetus was highly sensitive to the inhibitor alpha-amanitin. On the other hand, RNAP III, identified by its sensitivity to the specific inhibitor tagetitoxin, was found to be resistant to alpha-amanitin in Tritrichomonas foetus, but showed a typical intermediate sensitivity in T. vaginalis. Extension of this study to an additional seven trichomonad species confirmed this genera specific pattern of alpha-amanitin sensitivity and highlighted an unusual diversity in RNAPs among trichomonads, a closely related group of unicellular eukaryotes.
Keywords: Trichomonas vaginalis; Dicarboxylic Acids; Organophosphorus Compounds; Enzyme Inhibitors; zvířata; inhibitory enzymů; Trichomonadida; Animals; kyseliny dikarboxylové; RNA-polymerasa II; Cell Membrane Permeability; Transcription, Genetic; RNA protozoální; Amanitins; lysofosfatidylcholiny; genetická transkripce; RNA, Protozoan; Lysophosphatidylcholines; permeabilita buněčné membrány; organofosforové sloučeniny; amanitiny; RNA Polymerase II; Tritrichomonas foetus